Strategi pengambilan keputusan di lingkungan pesantren: Studi kasus pada pesantren Darul Falah Ternate - Nisa, Akramun; Andy, Andy; Asmiraty, Asmiraty (MAN 4 Kota Pekanbaru, 2025)
his study aims to examine the dynamics of modernization in the management of Pondok Pesantren Darul Falah Ternate and to analyze the extent to which these changes influence the characteristics and existence of the pesantren. The background of this research lies in the social transformation and the demands of the times, which require pesantren to adapt without abandoning their religious identity. This study employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The findings show that modernization at Pondok Pesantren Darul Falah includes the development of an educational management system, the integration of general and religious curricula, and the use of information technology. Nevertheless, the traditional values of the pesantren are still upheld as the foundation for students’ character formation. The study concludes that modernization does not negate the essence of the pesantren, but rather strengthens its role as an adaptive Islamic educational institution. The implications of this study highlight the importance of inclusive and visionary managerial strategies for enabling pesantren to transform sustainably in facing global challenges.